2017
DOI: 10.1111/jnc.13932
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia/ischemia activate processing of Amyloid Precursor Protein: impact of vascular dysfunction in the pathogenesis of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is associated with deficiencies in cerebrovascular functions, e.g. reduced cerebral blood flow and capillary amyloid angiopathy, both of which are evident during the early phase of AD, thus local hypoxia/ischemia could augment the pathogenesis of AD. There is abundant literature revealing that exposures to hypoxia/ischemia increase the amyloidogenic processing of amyloid-b precursor protein (APP) leading to the accumulation of amyloid-b peptides in brain. This hypoxia-induced response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(150 citation statements)
references
References 179 publications
(363 reference statements)
3
146
1
Order By: Relevance
“…This raises the question, however, of whether this treatment directly impacts AD pathophysiology or may it just treat an atherosclerotic comorbidity. There is evidence directly linking hypoxia to amyloidogenic processing of the amyloid-β protein precursor (AβPP) [52]. Hypoxia-inducible factor-1α (HIF-1α) leads to increased β-secretase 1 (BACE-1) transcription, which occurs through HIF-1α binding to the hypoxia-responsive element in the promotor region of the BACE-1 gene [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises the question, however, of whether this treatment directly impacts AD pathophysiology or may it just treat an atherosclerotic comorbidity. There is evidence directly linking hypoxia to amyloidogenic processing of the amyloid-β protein precursor (AβPP) [52]. Hypoxia-inducible factor-1α (HIF-1α) leads to increased β-secretase 1 (BACE-1) transcription, which occurs through HIF-1α binding to the hypoxia-responsive element in the promotor region of the BACE-1 gene [53].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor-1α (HIF-1α) leads to increased β-secretase 1 (BACE-1) transcription, which occurs through HIF-1α binding to the hypoxia-responsive element in the promotor region of the BACE-1 gene [53]. While BACE-1 cleavage of AβPP is the rate limiting step in amyloid-β production, hypoxia and ischemia also increases expression and activation of γ-secretase through multiple proposed mechanisms [52]. In addition to hypoxia enhancing the amyloidogenic pathway of AβPP processing, there is also evidence that it inhibits the non-amyloidogenic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypoxic conditions are thought to increase the accumulation of Aβ peptides through the activation of BACE1 and γ-secretase [307]. Additionally, disruption of the blood–brain barrier has been suggested to impair clearance of Aβ peptides from the brain [48].…”
Section: Vascular Dysregulationmentioning
confidence: 99%
“…Furthermore, hypoxia and ischemia activates processing of amyloid precursor protein and plays a crucial role in the pathogenesis of AD (Salminen et al, 2017). Several investigations using cellular models and in vivo studies have revealed that expression and activity of neprilysin (NEP), which is an Aβ-degrading enzyme, declines with age and also under hypoxic/ischemic conditions.…”
Section: Hypoxia/ischemia In Cns Pathologiesmentioning
confidence: 99%